Bioefficacy of saponin nano-emulsion formulation against Pomacea maculata, pest of rice - Zafri, Azim Syahmi (2017)
As the staple food in Malaysia, rice is being consumed routinely by Malaysian to provide a huge fraction of the needs for energy-rich materials. Thus, rice is planted widely all over the country. However, one of the biggest problem in growing rice is pest infestation, especially the more commonly known as apple snails, Pomacea spp. Apple snails bring damage by destroying rice seedlings. However, younger seedlings are more susceptible to attacks. Many methods have been adopted to control this major pest of rice. But the use of chemical molluscicide is the most favoured method by farmers due to its effectiveness. On the negative side, chemical molluscicide is hazardous to the environment, and may also jeopardize public health. In effort to create a safer alternative to chemical molluscicide, a formulation of biomolluscicide in the form of nano-emulsion was tested on Black Apple Snails, Pomacea maculata (Perry) to test its efficacy. The biomolluscicide was formulated using saponin, a natural glycoside extracted from plant as its active ingredient and called saponin nano-emulsion formulation. Five different treatments (2000, 1000, 750, 500 and 250 ppm) were tested including one positive and negative control. All of the treatments were replicated five times and arranged in Completely Randomized Design (CRD). MR219 rice seedlings were planted continuously to feed the apple snails. Two bioassays were conducted. The first one is the mortality bioassay. During this bioassay, mortality of apple snails were observed after 24, 48 and 72 hours. Percentage mortality of apple snail within each treatment were obtained by evaluating the data using Analysis of Variance (ANOVA). Meanwhile, feeding deterrent bioassay was also conducted to observe the mean of leaf area consumed by P. maculata for each treatment within 24 hours. Data of the feeding deterrent bioassay were also analysed using ANOVA. The overall result obtained proved that, saponin nano-emulsion formulation has a great potential be used as a substitute to the hazardous synthetic molluscicides for the purpose of controlling P. maculata in rice field.